PENGEMBANGAN PEMBELAJARAN PENJASORKES PADA MATERI MENERAPKAN BUDAYA HIDUP SEHAT MENGGUNAKAN MEDIA KARTU PINTAR UNTUK SISWA KELAS IV DI SDN SEKARAN 01 KECAMATAN GUNUNG PATI KOTA SEMARANG TAHUN 2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study is to produce a model of learning application development using the media culture of healthy living smart card for fourth grade students at SDN 01 Sekaran District of Mount Pati Semarang. Model development of learning materials budya penjasorkes on healthy living by using a smart card media is done through the procedure with several stages of the development of needs analysis, initial product manufacturing, product testing, product revision first, field testing, revision of the final product, the final result of the learning model penjasorkes in applying the material culture of healthy living with a smart card media. Based on the assessment results of a small pilot group, the cognitive aspects obtained an average percentage of 84.2% and includes a good assessment categories. In the affective aspect obtained an average percentage of 90% and includes penialaian Both categories. The results of field trials, the cognitive aspects of obtained average percentage of 97.9% and includes the Excellent rating category. These results indicate that the model of learning development penjasorkes on applying the material culture of healthy living by using the media card can be used for the fourth grade students of SDN 01 Sekaran District of Mount Pati, Semarang.